2021
DOI: 10.1038/s41598-021-92457-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water absorption on the mechanical properties of hybrid natural fibre/phenol formaldehyde composites

Abstract: This investigation is carried out to understand the effects of water absorption on the mechanical properties of hybrid phenol formaldehyde (PF) composite fabricated with Areca Fine Fibres (AFFs) and Calotropis Gigantea Fibre (CGF). Hybrid CGF/AFF/PF composites were manufactured using the hand layup technique at varying weight percentages of fibre reinforcement (25, 35 and 45%). Hybrid composite having 35 wt.% showed better mechanical properties (tensile strength ca. 59 MPa, flexural strength ca. 73 MPa and imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 148 publications
(87 citation statements)
references
References 45 publications
4
70
0
Order By: Relevance
“…As discussed earlier, the susceptibility of natural fiber-based composites to moisture/water has been well reported in the literature for different matrices [ 7 , 8 , 9 , 10 , 11 , 34 , 35 ]. Recently, Sanjeevi et al [ 35 ] have reported that for a hybrid phenol formaldehyde system with Areca fine fibers and Calotropis Gigantea fibers, the higher the natural fiber content in the composite, the higher was the water absorption rate. They have noted a 4.3% water absorption with 45 wt.% of fiber loading.…”
Section: Resultsmentioning
confidence: 88%
“…As discussed earlier, the susceptibility of natural fiber-based composites to moisture/water has been well reported in the literature for different matrices [ 7 , 8 , 9 , 10 , 11 , 34 , 35 ]. Recently, Sanjeevi et al [ 35 ] have reported that for a hybrid phenol formaldehyde system with Areca fine fibers and Calotropis Gigantea fibers, the higher the natural fiber content in the composite, the higher was the water absorption rate. They have noted a 4.3% water absorption with 45 wt.% of fiber loading.…”
Section: Resultsmentioning
confidence: 88%
“…[ 61–65 ] Hybrid composites were used to reduce the higher moisture absorption and also to increase the mechanical properties. [ 66–69 ]…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of the fibre-reinforced composites could be modified on the basis of requirements by altering the fibre-resin-filler combination [18]. The renewable, cheap, non-abrasive nature of jute-fibre makes it an attractive option for use as reinforcement in composites.…”
Section: Introductionmentioning
confidence: 99%